Kim jesteśmy? Kim będziemy? Poszukiwanie tożsamości emigracyjnej w My zdies' emigranty Manueli Gretkowskiej - Boczkowska, Magdalena (Tematy i Konteksty, 2011)
The article analyses a novel My zdies’emigranty by Manuela Gretkowska published in 1992. The main focus falls on the problem of émigré identity which the generation that left Poland in 1988 was forced to face. Gretkowska undertakes an attempt to describe her image of political émigré who leads a peculiarly nomadic life. His main features are lack of a permanent address and unwillingness to put down roots. Gretkowska, the author of Europejka, depicts a variety of emigrant groups with their different ‘émigré identities’. The first one consists of Polish émigrés who long for their homeland and want to return there. The second group unites those who reject their Polish identity and make a symbolic attempt to ‘flush their Polish passport down the Seine River’. The third group consists of nomads who are always ready to pack up, depart and live wherever they like or anywhere their fate places them. The described by Gretkowska Paris episode can also be found in her latest book entitled Trans. The final paragraphs of the article mention other novels undertaking the subject of contemporary émigrés as well. Here the main focus falls on Zapiski szwedzkie from Własne miejsca by Katarzyna Tubylewicz. According to the author of the article, Tubylewicz and Gretkowska describe similar observations of the émigré identity of Poles.